Perspektif Agama Kristen Terhadap Keadilan Masa Kini Menurut Kitab Matius 20 :1-16 - Reni Marlince Adang; Aprianus Moimau (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
Parable of Jesus and Matthew 20:1-16 In this parable, Jesus welcomes the first kingdom as the employer of much of the last work and a number of trainings. This shows that God's grace is not limited and does not depend on human effort or achievement, but on his generosity. In the context of Christianity This modern view is the importance of grace, loyalty and justice in society. God's grace shows that every person, whatever their background and origin, has the same value in His eyes. Therefore, Christians are called to practice kindness and social justice in their daily lives, providing care and support to those who require carelessness from the circumstances or conditions they have achieved but this view also challenges the attitudes and feelings of superiority that can arise among Christiansı the teachings of Jesus emphasize that the Kingdom of heaven does not depend on human concepts of justice but on God's mercy that goes beyond the limits of human ability. This is why Christians abandon their selfish attitudes and develop a broader development of God's liberating love because of religious understanding. Modern Christians based on Matthew 20:1-16 emphasize the importance of grace, faithfulness and justice in society while they recognize the habit of seeking egoism and develop a broader understanding of God's infinite love